Hyper-chaotic LÜ System Simulation Design of Digital Circuit Based on DSP Builder - Zhang Xiaohong; Zhang Zhiguang (Institute of Advanced Engineering and Science, 2013)
In order to overcome sensitive defects of components deviations and environment defects in analog circuit design, a novel four-dimensional hyperchaotic systems is constructed based on LÜ system. Basic nonlinear dynamics characteristics are analyzed to the new system. By optimizing the design of sampling frequency selection, gain adjustments, parameter configuration etc., the hyperchaotic circuit runs stably while the signal amplitude is reasonably controlled. Curves of the digital chaotic sequence show smooth without jagged shape. The circuit can be applied to other digital realization of chaotic systems with commonality and expandability. Its experimental results fully consistent with phase space structures of the continuous chaotic system, which shows the development of chaotic systems based on FPGA is feasible and practical. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2503